Extensive emphysematous pyelonephritis in a renal allograft: case report and review of literature. Issue 4 (2nd July 2014) - Ágreda Castañeda, F.; Lorente, D.; Trilla Herrera, E.; Gasanz Serrano, C.; Servian Vives, P.; Iztueta Saavedra, I.; Morote Robles, J.
Abstract Emphysematous pyelonephritis (EPN) is an acute, severe necrotizing infection of the renal parenchyma and perirenal tissue, which results in the presence of gas within the renal parenchyma, collecting system, or perinephric tissue. EPN of renal allograft is rare, with only 23 cases reported in Western literature. Here, we report a patient treated successfully with surgery. We also review the literature, focusing on old and new suggested classification systems for EPN.